PARAMETER POPULASI IKAN BETOK (Anabas testudineus (BLOCH, 1792)) DI EKOSISTEM PAPARAN BANJIR SUNGAI MUSI, Lubuk Lampam - Nurdawati, Syarifah; Fahmi, Zulkarnaen; Supriyadi, Freddy (Research Center for Biology-Indonesian Institute of Sciences, 2019)
Anabas testudineus Bloch, 1792 is economically important fish species found in Lubuk Lampam floodplains of Musi River. Fishing activities that take place throughout the year can affect reproduction patterns and recruitment (new additions) of fish. This study aims to evaluate several parameters of betok fish populations that can be used as input for fish resource management policies in floodplains of Musi river. A total of 3271 samples of betok fish caught by fishermen from March to November 2011 were collected to obtain data on fish length and weight. Growth parameters (L∞, K, Z dan M) were calculated using FiSAT II based on the length frequency distribution of fish. The values of L∞ and K were obtained at 204.75 mm and 0.24 / year respectively while the maximum age of fish was estimated to be 4.36 years. The total mortality (Z) and natural mortality (M) of betok fish is 0.99 / year and 0.42 / year, Fishing mortality (0.56/year). The exploitation rate (0.57) was slightly lower than the predicted value (Emax= 0.69) indicating that Anabas testudineus was near fully exploited in the Lubuk Lampam floodplain ecosystem.